Pemberdayaan kader posyandu lansia melalui edukasi diabetes melitus untuk meningkatkan pencegahan dan perawatan lansia - Indriyati Indriyati; Rantiningsih sumarni; Atik Aryani; Khasanah Nur Giang; Yessy Nur Istiqomah (Penamas: Journal of Community Service, 2026)
Diabetes Mellitus (DM) is a chronic metabolic disease characterized by elevated blood glucose levels due to impaired insulin secretion, insulin action, or both. Many older adults are unaware that they have diabetes until they experience complications such as heart disease, stroke, kidney problems, or diabetic wounds that are difficult to heal. The Elderly Integrated Health Post (Posyandu) is a community-based health service that functions to maintain, monitor, and improve the health status of older adults at the village or sub-district level. This community service activity aims to increase the capacity and independence of Posyandu elderly cadres in providing education and assistance related to prevention, dietary management, and basic care for older adults with Diabetes Mellitus, thereby improving the quality of life of the elderly and reducing the risk of DM complications in the community. The method of this activity is to provide education and training to elderly cadres on prevention, diet, and care for older adults with DM. The results of this activity showed that knowledge before the education was mostly sufficient (60%), and after the activity, participants' knowledge increased, and the majority (80%) were classified in the good knowledge category.